Brain aging differs with cognitive ability regardless of education - Kristine B. Walhovd; Lars Nyberg; Ulman Lindenberger; Inge K. Amlien; Øystein Sørensen; Yunpeng Wang; Athanasia M. Mowinckel; Rogier A. Kievit; Klaus P. Ebmeier; David Bartrés-Faz; Simone Kühn; Carl-Johan Boraxbekk; et al. (Scientific Reports, 2022)
Abstract Higher general cognitive ability (GCA) is associated with lower risk of neurodegenerative disorders, but neural mechanisms are unknown. GCA could be associated with more cortical tissue, from young age, i.e. brain reserve, or less cortical atrophy in adulthood, i.e. brain maintenance. Controlling for education, we investigated the relative association of GCA with reserve and maintenance of cortical volume, -area and -thickness through the adult lifespan, using multiple longitudinal cognitively healthy brain imaging cohorts (n = 3327, 7002 MRI scans, baseline age 20–88 years, followed-up for up to 11 years). There were widespread positive relationships between GCA and cortical characteristics (level-level associations). In select regions, higher baseline GCA was associated with less atrophy over time (level-change associations). Relationships remained when controlling for polygenic scores for both GCA and education. Our findings suggest that higher GCA is associated with cortical volumes by both brain reserve and -maintenance mechanisms through the adult lifespan.